The relationship between career growth opportunity and turnover intentions in employees in startup companies x: career planning coaching program designed as an intervention - Widya Syayidatus Solihat; Alice Salendu (Gema Wiralodra, 2023)
This research was conducted to look at the correlation of each dimension of career growth opportunity to turnover intentions at the startup company PT X. This research uses a quantitative approach involving numerical data analysis using special statistical techniques. The population in this study are employees at Startup X Company, with a total of 530 employees. The research sample was taken using a convenience sampling technique. The results of this study indicate that career growth opportunities have a significant negative correlation with turnover intention. Two of the four dimensions of career growth opportunity, namely career goals progress and promotion speed, correlate with turnover intention. Employees who receive promotion and career advancement opportunities the company provides tend to have lower intentions to leave the company. Factors such as organizational structure and employment level influence employees' perceptions of career growth opportunities. Employee gender also plays a role in perceptions of career growth opportunities. However, no significant correlation was found between employee age, career growth opportunity, and turnover intention variables. Based on the results of the data processing and analysis that has been carried out, it can be concluded that Career growth opportunity shows significant correlation results with turnover intention among employees at PT X Startup, and there are two dimensions of career growth opportunity.